2023
DOI: 10.3390/atoms11100128
|View full text |Cite
|
Sign up to set email alerts
|

The Fingerprints of Periodic Electric Fields on Line Shapes Emitted in Plasmas

Ibtissem Hannachi,
Roland Stamm

Abstract: Periodic electric fields are found in many kinds of plasmas and result from the presence of collective fields amplified by plasma instabilities, or they are created by external sources such as microwave generators or lasers. The spectral lines emitted by atoms or ions in a plasma exhibit a frequency profile characteristic of plasma conditions, such as the temperature and density of charged particles. The fingerprints of periodic electric fields appear clearly on the line shape for a large range of frequencies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Specifially, it was shown that the usual formula employed in calculations without an external field, which assumes stationarity, does not recover the correct Blokhintsev limit. For small fields, this does not make much of a difference [29], but it can be important for larger fields. It was also shown that dressing either electrons or ions alone is theoretically suspect, that random phases of the oscillatory electric fields do not alter the satellite positions and intensities-something that is also numerically convenient-but they do in principle affect the width and that stiffness may be an issue, which may be handled by solving once and for all by computing the atomic plus oscillatory field time evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Specifially, it was shown that the usual formula employed in calculations without an external field, which assumes stationarity, does not recover the correct Blokhintsev limit. For small fields, this does not make much of a difference [29], but it can be important for larger fields. It was also shown that dressing either electrons or ions alone is theoretically suspect, that random phases of the oscillatory electric fields do not alter the satellite positions and intensities-something that is also numerically convenient-but they do in principle affect the width and that stiffness may be an issue, which may be handled by solving once and for all by computing the atomic plus oscillatory field time evolution.…”
Section: Discussionmentioning
confidence: 99%